Family Harmonization and Adoption Of Religious Moderation Values As Efforts To Prevent Non-Harmony Family - Hilal, Fatmawati (Jurnal Al-Qadau: Peradilan dan Hukum Keluarga Islam, 2023)
The family as the smallest institution in society is the main foundation for realizing a harmonious family which becomes the forerunner to the peaceful country. A harmonious family is the ideals and hopes of every family. This paper describes the importance of family harmonization by adopting the values ​​of religious moderation as an effort to prevent the non-harmonious families. This paper uses qualitative research methods with a syar’i approach. The results found that the concept of religious moderation, such as tawassuth (taking the middle way), tawazun (balanced), I’tidal (straight and firm), tasamuh (tolerance), musawah (egalitarian), syuira (deliberation), Ishlah (reform), aulawiyah (prioritizing priority), and tathawwur wal ibtikar (dynamic and innovative). If these values ​​of religious moderation are internalized and adopted in family life, they will facilitate the creation of a harmonious family. The values ​​of religious moderation give the concept of mutuality (mubilah) in the family. No forcing, respecting each other’s rights, upholding the principle of complementarity, deliberation in making decisions are values ​​of moderation that will facilitate the creation of a harmonious family. Internalization and adoption of the value of religious moderation in the family can build a strong foundation, create a harmonious environment, and prevent cases of broken homes that have the potential to damage family life and society. Keyword : Harmozation, Family, Religious Moderation